2008
DOI: 10.1007/s00394-008-0696-9
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer risk associated with selenium status is modified in smoking individuals by Sep15 polymorphism

Abstract: It appears that among smoking individuals, those with the Sep15 1125 AA genotype may benefit most from a higher Se intake, whereas in those with the GG or GA genotype, a higher Se status may increase the risk for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 30 publications
2
58
1
Order By: Relevance
“…Rs5845 and rs5859 are SNPs in a region of the SEP15 gene corresponding to the 3 0 UTR; they are closely linked, and their modulation of the ability of the 3 0 UTR to promote reporter gene activity [13] indicates that they have functional consequences. Furthermore, the SNPs have been reported to affect breast cancer risk [13] and risk of lung cancer in smokers [14]. The present results indicate that the SNPs influence rectal cancer risk in men.…”
Section: Discussionsupporting
confidence: 65%
“…Rs5845 and rs5859 are SNPs in a region of the SEP15 gene corresponding to the 3 0 UTR; they are closely linked, and their modulation of the ability of the 3 0 UTR to promote reporter gene activity [13] indicates that they have functional consequences. Furthermore, the SNPs have been reported to affect breast cancer risk [13] and risk of lung cancer in smokers [14]. The present results indicate that the SNPs influence rectal cancer risk in men.…”
Section: Discussionsupporting
confidence: 65%
“…Another meta-analysis of epidemiological data concluded that despite evidence for an inverse association between Se exposure and the risk of some types of cancer, these results should be interpreted with care due to the potential limiting factors of heterogeneity and influences of unknown biases (79). One of these factors is genetic background-a study among smokers demonstrated that depending on a 15-kDa selenoprotein genetic polymorphism, smoking individuals either can benefit from a higher Se intake or have an increased risk for lung cancer (161). Together, the results from a number of ongoing randomized controlled trials (79,119) should help to better understand the general effect of selenium in cancer.…”
Section: E Seleniummentioning
confidence: 99%
“…4 Sep15 polymorphism is associated with lung cancer. 283 GPx2 is upregulated in some types of cancer, particularly of gastrointestinal origin. 284 A recent study has shown that lower expression of GPx2 increases migration and invasion of cancer cell clones, but decreases their growth, thus depending on the stage of tumour development.…”
Section: Male Infertilitymentioning
confidence: 99%